1996
DOI: 10.1364/ol.21.001738
|View full text |Cite
|
Sign up to set email alerts
|

Observations of backscattering effects in second-harmonic generation from a weakly rough metal surface

Abstract: We present experimental observations of diffusely scattered second-harmonic light from a silver surface with weak random roughness. The roughness provides coupling of the incident wave to counterpropagating surface plasmon polaritons in the second harmonic. Rather than observing enhancement in the backscattering direction, a distinct minimum in the angular distribution is seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The distribution is quite different from the Gaussian case and the various features seen arise from different perturbation terms of Eq. (8). The scatter for θ s ≤ −°36 is due largely to the 1-1 term, though other higher-order terms also make contributions there.…”
Section: Numerical Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The distribution is quite different from the Gaussian case and the various features seen arise from different perturbation terms of Eq. (8). The scatter for θ s ≤ −°36 is due largely to the 1-1 term, though other higher-order terms also make contributions there.…”
Section: Numerical Resultsmentioning
confidence: 95%
“…(4-6) are inserted into Eq. (8). The resulting moments of ζ are expanded with the assumption that h x ( ) is a real Gaussian process and, particularly in the higher orders, many terms are thus obtained.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…The results of these calculations showed that either a peak or a dip can occur in the retroreflection direction in the angular dependence of the intensity of the second harmonic light depending on the values of the phenomenological constants entering the nonlinear boundary conditions, and on the angle of incidence, and that there is no real peak in the direction normal to the mean surface. The experimental observation that only a dip occurs in the retroreflection direction for all angles of incidence 115,116 places significant constraints on the values of the phenomenological constants in the nonlinear boundary conditions. Surface plasmon polaritons were shown to play a prominent role in the formation of the features observed in the retroreflection direction, which were attributed to the nonlinear excitation of these surface waves at the harmonic frequency.…”
Section: Second Harmonic Generation At Clean Vacuum-metal Interfacesmentioning
confidence: 99%
“…The scattering data were absolutely normalized, which permits quantitative comparisons of experimental and theoretical results to be made. It was found that for both weakly 115,116 and strongly 117 rough surfaces a dip is present in the retroreflection direction in the angular dependence of the intensity of the scattered second harmonic light rather than the peak that occurs in scattering at the fundamental frequency. No peak in the direction normal to the mean surface was observed in these experiments.…”
Section: Second Harmonic Generation At Clean Vacuum-metal Interfacesmentioning
confidence: 99%
“…The occurrence of large surface EM fields is indeed crucial to the EM mechanism in Surface-Enhanced Raman Scattering (SERS) and to other non-linear surface optical processes. [26,29,30,31,32,38,39] Furthermore, the predicted, enormously high values of the surface electric field intensity have been related to the recent observation of SERS single molecule probing. [40,41,42] It is our aim to employ the above mentioned rigorous Green's theorem formulation to study the far-field and near-field scattered from one-dimensionally rough, self-affine fractal Ag surfaces, restricted to one dimension for the sake of computational limitations.…”
Section: Introductionmentioning
confidence: 97%